2015
DOI: 10.1037/lhb0000120
|View full text |Cite
|
Sign up to set email alerts
|

Misinterpreting eyewitness expressions of confidence: The featural justification effect.

Abstract: How do we know eyewitness statements of confidence are interpreted accurately by others? When eyewitnesses provide a verbal expression of confidence about a lineup identification, such as I'm fairly certain it's him, how well do others understand the intended meaning of this statement of confidence? And, how is this perception of the meaning influenced by justifications of the level of confidence, such as when eyewitnesses say, I remember his chin? The answers to these questions are unknown, as there is no res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
88
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(105 citation statements)
references
References 52 publications
(61 reference statements)
14
88
2
Order By: Relevance
“…A similar conclusion can be drawn by a different research line on the featural justification effect: participants presented with a witness identification and an estimation of confidence accompanied by a featural justification (e.g., I recognize his chin) underestimate the actual confidence intended by the witness (Dobolyi & Dodson, ; Dodson & Dobolyi, , ). This featural justification effect is explained by the fact that in a fair lineup a particular physical feature will likely not differentiate between faces and, thus, will be perceived by participants as nondiagnostic of the accuracy of the identification.…”
supporting
confidence: 68%
“…A similar conclusion can be drawn by a different research line on the featural justification effect: participants presented with a witness identification and an estimation of confidence accompanied by a featural justification (e.g., I recognize his chin) underestimate the actual confidence intended by the witness (Dobolyi & Dodson, ; Dodson & Dobolyi, , ). This featural justification effect is explained by the fact that in a fair lineup a particular physical feature will likely not differentiate between faces and, thus, will be perceived by participants as nondiagnostic of the accuracy of the identification.…”
supporting
confidence: 68%
“…The answer is no; for both low and high confidence responses, the CAC plots for these scale types led to similar accuracy. Dodson and Dobolyi ( 2015b , 2017 ), however, have reported that verbal confidence statements, especially ones accompanied by a justification, increased variability in observers’ (e.g. police or jurors) interpretation of those confidence statements.…”
Section: Discussionmentioning
confidence: 99%
“…These plots permit us to ask questions such as, “Is 5 on a 5-point scale equivalent to 17–20 on a 20-point scale and to 81–100 on a 100-point scale in terms of accuracy?” Of course, we can ask this question for all points on the confidence scale (“Is a 2 on a 4-point scale equivalent to 6–10 ratings on a 20-point scale and 26–50 on a 100-point scale?”). One essential difference between the present study and that of Dodson and Dobolyi ( 2015 ) is that we used confidence scales over a wide range (4-, 5-, 20-, and 100-point scales) rather than carving up a 100-point scale in different ways. At issue is whether subjects will use these widely different confidence scales in the same way or in different ways.…”
Section: Introductionmentioning
confidence: 97%
“…More directly relevant to our present project, Dodson and Dobolyi ( 2015 ) compared nine confidence scales using lineup identifications as recognition tests. They employed verbal and numeric scales (e.g., ranged from 0 to 100 or from “not at all confident” to “completely confident”) and different numbers of points identified on a 100-point scale (e.g., numeric 6 points, 0–100: 0, 20, 40, 60, 80, or 100).…”
Section: Introductionmentioning
confidence: 99%